Influence of public service motivation on job satisfaction and organisational commitment of quantity surveyors in Nigerian public service / L. O. Oyewobi - Oyewobi, L. O. (Research Management Institute (RMI), 2013)
Public Service Motivation (PSM) has been reported to have significant influence on employees’ work attitudes. The study samples the opinion of Quantity Surveyors (QS) in Nigeria FederalMinistries and Parastatals by adopting PSM construct questionnaire template used by previous researchers to investigate the impact of PSM on job satisfaction and organizational commitment amongst QS. The data were subjected to descriptive statistics and correlation analysis, to precipitate major variables that exhibit significant impact on job satisfaction, organisational commitment and PSM amongst QS working in Nigerian public sectors. The research revealed that QS in public service are more satisfied with their job when adequate recognition is given and opportunities for advancement are encouraged. The result of the correlation also showed that strong positive relationship existed between job satisfaction and public interest and also between organizational commitment and self sacrifice with the r-value of 89% and 92% respectfully. The research recommended that advancement opportunity in career progression and professional development such as in-house training should be encouraged to improve quality service delivery and that PSM should be seen as a vital instrument that could be employed to search for individuals who are best suited and ready to render selfless service for public work.